Aramaic Letters and Neo-Assyrian Letters: Philological and Methodological Notes - Fales, Frederick Mario
468-469: Appendix: klby’ (AP 30, 16): loanword from late Akkadian, kall?p/bu, "light troops, auxiliaries".